Epidemiology and Antimicrobial-Resistant Genes of Family Staphylococcaceae in Musca domestica: Case Studies from Chicken Farm, Pig Farms, and Residential Areas in Southern Thailand - Narin Sontigun; Nattharee Thanawan; Punpichaya Fungwithaya (Insects, 2026)
The major Staphylococcaceae family is recognized as opportunistic pathogens colonizing human and animal skin, mucous membranes, and environments. Musca domestica, the house fly, plays a role in the transmission of AMR bacteria. This study focused on examining the epidemiology and antimicrobial-resistant genes of the family Staphylococcaceae in M. domestica through metagenomic analysis, using samples collected from three animal farms and two residential areas in southern Thailand. Fifty M. domestica were collected from five places surrounding Walailak University, including one chicken farm (CF1), two pig farms (PF2 and PF3), and two residential areas (H1 and H2). All samples were dispatched for analysis using shotgun metagenomic sequencing and analyzed using FastQC, MultiQC, FASTQ, MEGAHIT, QUAST, ABRicate, AMRFinderPlus, ResFinder, ARG-ANNOT, MEGARES, PlasmidFinder, VFDB, Kraken2, Krona and Python. Our findings describe the taxonomic composition of Staphylococcaceae taxa in M. domestica from different environments; the representation of the family Staphylococcaceae in CF1, PF2, PF3, H1, and H2 was recorded at 2%, 0.7%, 0.2%, 0.2%, and 2% of this phylum, respectively. The average populations discovered were Staphylococcus (37.4%), Mammaliicoccus (17.4%), and Macrococcus (10.3%), respectively. Trimethoprim-resistant genes (dfrG and dfrE) were found only in CF1, PF2, and H1. Interestingly, fosfomycin-resistant genes were found only in M. domestica within residential areas. Our findings pertain to the Staphylococcaceae population in M. domestica within residential areas, which exhibited varying multidrug-resistance genes, particularly those resistant to fosfomycin.
Keywords: Antimicrobial Resistance in Staphylococcus; Forensic Entomology and Diptera Studies; Microbial Metabolism and Applications